已知\( y = {e^{2x}} \),则\( y' \)为( ).
A: \( {e^x} \)
B: \( 2{e^x} \)
C: \( {e^{2x}} \)
D: \( 2{e^{2x}} \)
A: \( {e^x} \)
B: \( 2{e^x} \)
C: \( {e^{2x}} \)
D: \( 2{e^{2x}} \)
D
举一反三
- 函数\(y = {e^{ - {x^2}}}\)的导数为( ). A: \( - 2x{e^{ - {x^2}}}\) B: \(2x{e^{ - {x^2}}}\) C: \( - 2x{e^ { { x^2}}}\) D: \(2x{e^ { { x^2}}}\)
- 设\(z = u{e^v}\),\(u = {x^2} + {y^2}\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}({x^2}y + {y^3} + 2x)\) B: \({e^{xy}}({x}y^2 + {y^3} + 2x)\) C: \({e^{xy}}({x}y + {y^3} + 2x)\) D: \({e^{xy}}({x^2}y + {y^2} + 2x)\)
- 已知\( y = {x^2} + 2x \),则\( y' \)为( ). A: \( 2x + 2 \) B: \( 2x \) C: \( 0 \) D: \( x \)
- 下列函数为偶函数的是( )。 A: \( y = {2{e}^{2x}} - {2{e}^{ - 2x}} + \sin x \) B: \( y = {\log _a} { { 1 - x} \over {1 + x}} \) C: \( y = { { {e^x} + {e^{ - x}}} \over 2} \) D: \( y = 3{x^2} - {x^3} \)
- 已知\( y = {e^{2x + 1}} \),则\( y' \)为( ). A: \( 2{e^{2x + 1}} \) B: \( {e^{2x + 1}} \) C: \( {e^x} \) D: \( (2x + 1){e^{2x + 1}} \)
内容
- 0
下列函数为偶函数的是( )。 A: \( y = e^{2x} - {e}^{ - 2x} + \cos x \) B: \( y = {\log _2} { { 1 + x} \over {1 -x}} \) C: \( y = 3{x^4} - {x^3} \) D: \( y = { { {e^x} + {e^{ - x}}} \over 2} \)
- 1
已知\( {y^{(4)}} = {x^2} + 2x \),则\( {y^{(5)}} = 2x + 2 \)( ).
- 2
设 $y=\tan x^2$,则 $y'=$( ). A: $\sec x^2$ B: $\sec^2 x^2$ C: $2x\sec^2 x$ D: $2x\sec^2 x^2$
- 3
函数\(y = \sin{x^2}\)的导数为( ). A: \( - 2x\sec {x^4}\) B: \(2x\cos {x^2}\) C: \(2x\sec {x^2}\) D: \(- 2x\sec {x^2}\)
- 4
函数\(y = {2^x} + {x^2}\)的导数为( ). A: \({2^x} + \ln 2.2x\) B: \({2^x} + 2x\) C: \({2^x}\ln 2 + 2x\) D: \( { { {2^x}} \over {\ln 2}} + 2x\)